Removal of Ni2+, Cu2+ and Zn2+ Using Different Agricultural Residues: Kinetics, Isotherm Modeling and Mechanism via Chemical Blocking - Singh, Joginder; Ali, Amjad; Kumar, Raman (Asian Journal of Chemistry, 2013)
Four different combinations, prepared by mixing various amounts of Trifolium alexandrinum biomass powder (TABP), Arachis hypogea shell powder (AHSP) and Eucalyptus cameldulensis saw dust (ESCD) were studied for the removal of Ni2+, Cu2+ and Zn2+ from aqueous solutions. The highest adsorption capacity of Ni2+, Cu2+ and Zn2+ was found to be 92.52, 94.12 and 96.75 mg g-1, respectively. The adsorption kinetics of all the three metals were relatively fast attaining the equilibrium within 300 min and were best described by pseudo-second order kinetics. The adsorption equilibrium followed Freundlich and Langmuir adsorption isotherm models. The FTIR study revealed that carboxyl and hydroxyl functional groups were mostly accountable for the removal of Ni2+, Cu2+ and Zn2+. The blocking of carboxyl and hydroxyl groups of the combination A [TABP (30%) + ESCD (35 %) + AHSP (35 %)] was done and it was found that more than 70 % removal of Ni2+, Cu2+ and Zn2+ were due to the contribution of carboxylic group, whereas less than 30 % removal of the same metal ions were due to the hydroxyl group. The release of Na+, K+, Mg2+, Ca2+ and H+ from the combination A with the equivalent uptake of Ni2+, Cu2+ and Zn2+ supported ion exchange as the foremost mechanism of adsorption. The column studies were carried out with electroplating wastewater containing Ni2+, Cu2+ and Zn2+ metal ions. Thomas model was applied to evaluate the metal uptake capacity for Ni2+, Cu2+ and Zn2+ and at the breakthrough points, the columns were recharged using 0.1 M HCl for three successive sorption-desorption cycles without much loss in the initial sorption capacity of the combination used. In brief, it can be concluded that the adsorbents used in different combinations are attractive and are alternative options for desalinating the heavy metal from industrial effluents.